بيع المزايدة: دراسة مقارنة في الفقه الإسلامي - الفقي، محمد عبدالفتاح محمد (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بدمنهور, 2020)
بيع المزايدة من البيوع التي احتاجها الناس قديما ويحتاجونها حديثا، وقد اشتمل هذا البحث: بيع المزايدة (دراسة مقارنة في الفقه الإسلامي) على ثلاثة مباحث ذكرت في الأول منها: تعريف بيع المزايدة وبيان نفعه وضرره وأقسامه وكيفية تنفيذه، وذكرت في المبحث الثاني البيوع المنهي عنها التي فيها شبه ببيع المزايدة وهي: السوم على سوم أخيه، وبيع المسلم على بيع أخيه، والبيع الذي فيه النجش، وبينت في المبحث الثالث حكم بيع المزايدة، والتوفيق بين حكمها وبين بيوع محرمة فيها شبه ببيع المزايدة، وحكم المزايدة بعد ركون البائع لأحد المزايدين، وذكرت إجابة لهذه الأسئلة: هل يدخل خيار المجلس بيع المزايدة؟ وهل يلزم العقد الزائد قبل أن يتم البيع؟ وبينت أحكام السمسار والدلال، وحكم أخذ العربون في المواعدة على البيع والشراء، وأجبت على هذا السؤال: هل يدخل خيار العيب بيع المزايدة؟ وبينت حكم البيع بالبراءة، وذكرت جوابا لهذا السؤال: هل لمن غبن في المزايدة خيار الغبن، وختمت المبحث الثالث ببيان رسم الدخول أو كراسة الشروط، وختمت البحث بخاتمة ضمنتها أهم نتائج البحث.
Selling bidding is one of the sales that people needed in the past and need them recently. This research included: Selling bidding (a comparative study in Islamic jurisprudence) on three topics mentioned in the first of them: definition of selling the bid and explaining the benefit and harm and its sections and how to implement it, and mentioned in the second topic the sales that are forbidden In which he likened to selling the bid, which is: Somme against the poison of his brother, the sale of a Muslim over the sale of his brother, and the sale in which there is negligence. An answer to these questions stated: Does the board's option enter the bidding sale? Is the excess contract required before the sale is completed? The provisions of the broker and auctioneer indicated the ruling on depositors buying and selling dating, and I answered this question: Does the defect option enter the bidding sale? And I indicated the ruling of selling by innocence, and I mentioned an answer to this question: Is it for the one who did not bid in the bidding the option of injustice, and concluded the third topic with a statement of the entry fee or brochure of terms, and concluded the search with a conclusion included in the most important results of the search.
Keywords: الفقه الإسلامي -- التشريع الإسلامي -- الأحكام الفقهية -- بيع المزايدة -- الدراسات الفقهية